2008
DOI: 10.1002/em.20443
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the genotoxic effect of pesticides on greenhouse workers' lymphocytes

Abstract: In the present study, the genotoxic effects of commonly applied pesticides were evaluated using the alkaline comet assay (pH > 13). The amount of DNA damage (% DNA in tail) in peripheral lymphocytes of 49 male agricultural workers from Southern Poland were measured and compared to 50 men from the same area who had no previous occupational exposure to pesticides. No statistically significant differences in basal DNA damage were found between the study groups. In addition, exposure of peripheral blood lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…This effect might be attributed to induction of adaptive processes, due to the chronic exposure to low doses of radiation of the subjects in the last group. Studies of other laboratories on the repair capacity of nuclear power plant workers (Toili et al, 2002) or workers exposed to xenobiotics, lead or pesticides (Restreppo et al, 2000;Vodicka et al, 2004;Piperakis et al, 2009) have shown, similar to our results, that workers repair DNA damage more efficiently than the non-exposed controls. The authors attributed this phenomenon to adaptive response by the sub-chronic genotoxic exposures.…”
Section: Discussionsupporting
confidence: 88%
“…This effect might be attributed to induction of adaptive processes, due to the chronic exposure to low doses of radiation of the subjects in the last group. Studies of other laboratories on the repair capacity of nuclear power plant workers (Toili et al, 2002) or workers exposed to xenobiotics, lead or pesticides (Restreppo et al, 2000;Vodicka et al, 2004;Piperakis et al, 2009) have shown, similar to our results, that workers repair DNA damage more efficiently than the non-exposed controls. The authors attributed this phenomenon to adaptive response by the sub-chronic genotoxic exposures.…”
Section: Discussionsupporting
confidence: 88%
“…Although there are studies reporting that with the use of protective equipment, there is no increase in DNA damage from the pesticides exposure [ 68 , 69 , 70 ], we would hardly believe that 87% of participants in our study have lied to wear the protective equipment, and we do not accept that misuse or not wearing PPM and lying about that would explain significantly elevated levels of DNA damage in all three test systems applied, and in the same time not to have also inhibition in acetylcholinesterase levels. Carbajal-López et al [ 44 ] as in our study also demonstrated that exposure did not demonstrate correlation with DNA damage found in comet assay nor in micronucleus assay in buccal cells in Mexican agricultural workers from Guerrero.…”
Section: Discussionmentioning
confidence: 99%
“…Comet assay is also used in environmental monitoring (Cavallo et al, 2002) and eco-genotoxicological studies (Lee and Steinert, 2003). The great usefulness of this technique and its rapid spread among the researchers are due to several advantages in comparison with other techniques, such as; (i) it has been applied in a variety of eukaryotic cells in any organ, including plants and many prokaryotic cells, with successful results, (ii) it detects damage at the single-cell level, (iii) highly sensitive (50–15,000 breaks/cell), (iv) results are obtained on the same day, (v) damage can be detected in cycling as well as in noncycling cells, (vi) it is fast, simple and inexpensive, (vii) noninvasive technique, (viii) fresh or frozen samples are suitable, (ix) cell lines are suitable, (x) sample size is very small (from 10,000 to 50,000 cells) (Duez et al, 2003; Fairbairn et al, 1995; Macioszek and Kononowicz, 2004; Mamur et al, 2010; Kontek et al, 2010; Piperakis et al, 2009; Toyoizumi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%